The Effectiveness of Discharge Planning Implementation on The Quality of Life of Ischemic Stroke Patients: A Literature Review - Yunizabetri sy; Nurul Huda; Bayhakki Bayhakki (Jurnal Ners, 2026)
Stroke is one of the leading causes of disability and mortality worldwide, significantly affecting patients' quality of life. Patients with ischemic stroke require continuous care after hospital discharge to support recovery and prevent complications. Discharge planning is an essential strategy for ensuring continuity of care and facilitating patients’ transition from hospital to home. This study aimed to analyze the effectiveness of discharge planning on the quality of life of patients with ischemic stroke. An integrative literature review approach was employed by searching articles from PubMed, ScienceDirect, Wiley Online Library, Google Scholar, Semantic Scholar, ResearchGate, and BMC databases. The keywords used included discharge planning, transitional care, quality of life, and ischemic stroke. A total of 10 articles that met the predetermined inclusion and exclusion criteria were analyzed. The methodological quality of the selected studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. The findings indicated that discharge planning effectively improved the quality of life of patients with ischemic stroke by enhancing discharge readiness, self-care ability, rehabilitation adherence, functional recovery, and continuity of care. Furthermore, the integration of transitional care strategies was shown to reduce hospital readmission rates and improve patient outcomes. It can be concluded that discharge planning is an effective intervention that should be implemented in a structured, patient-centered, and sustainable manner to improve the quality of life of patients with ischemic stroke.